Amelioration of Aflatoxin B1-induced gastrointestinal injuries by Eucalyptus oil in rats (2019)
Background: Eucalyptus oil (EO), derived from Eucalyptus species, possesses vast remedial and healing properties, although its gut health-promoting properties have not been well investigated. In this study, we investigated the chemical composition of a commercial EO formulation and its potential role in protecting against aflatoxinmB1 (AfB1)-induced gastrointestinal damage in rats. Methods: Male Wistar rats were divided into six groups with eight rats each. Control rats were administered with the vehicle (1% Tween 80) for 14 days, while another group was exposed to two oral doses of AFB1 on days 12 and 14. Two other groups were pre-treated with oral doses of EO (50 and 100 mg/kg b.w.) for 14 consecutivedays, along with two oral doses of AfB1 (5 mg/kg b.w.) on days 12 and 14. The remaining two groups weretreated with EO alone at the two doses for 14 days. At the end of the experiment, blood samples, stomachand intestinal tissues were collected for measurement of oxidative stress and antioxidant parameters and lightmicroscopic examination. Results: Gas chromatography-mass spectrometry analysis revealed Eucalyptol (1, 8-cineole) as the main con stituent (67.48%) of the oil. AfB1 administration induced oxidative and inflammatory disturbances, indicated by significantly (p<0.05) increased serum nitric oxide level and myeloperoxidase activity; increased tissue contents of hydrogen peroxide, malondialdehyde and protein carbonyls, accompanied with corresponding histological alterations. AfB1 also induced significant (p<0.05) reductions in glutathione peroxidase and superoxide dismutase (SOD) activities. Treatment with EO produced significant improvements in the biochemical parameters as well as the appearance of the gastric and intestinal mucosa. EO alone, at the two doses tested did not produce any significant changes in the parameters investigated. Conclusion: The findings from this study showed that EO demonstrated protective activity against Aflatoxin induced toxicity in stomach and intestinal tissues and may thus find application in treatment of gastrointestinal disorders.